Articles of Agreement of the International Monetary Fund : Adopted at the United Nations Monetary and Financial Conference, Bretton Woods, New Hampshire, July 22, 1944. Entered into force December 27, 1945. Amended effective July 28, 1969...; amended effective April 1, 1978...; and amended effective November 11, 1992.... (International Monetary Fund, 1993)
Revised in 1993, this edition incorporates the Third Amendment of the Articles of Agreement. Reprinted in December 2004. Reprinted in January 2008 (200 copies).